Is Islamic Banking Social Performance Able to Maintain Stock Price Stabilization by Exploring the Role of Profitability As An Intervening Variable? - Furwanti, Reni; Adilla, Adilla; Qoyum, Abdul (Global Review of Islamic Economics and Business, 2024)
This study aims to analyze the effect of profitability as an intervening variable on the Islamic and social performance of Islamic Banking in order to maintain earnings per share. The purpose of maintaining earnings per share is to attract investors to invest in Islamic bank issuers. Therefore, this study also endeavors to forecast Islamic banking stock price volatility for companies listed on IDX and propose a framework for its mitigation. This framework considers the role of social performance in enhancing profitability, utilizing the path analysis method. This study focused on 3 Islamic banking companies (PNBS, BRIS, and BTPS) as a sample, using quarterly data specifically for the period of 2017 to 2021 with a purposive sampling method. In addition, Data sources include financial statements encompassing profit-sharing ratio, distribution of zakat, and distribution of qard al-hasan. Furthermore, this study employed an ARIMA regression model, subsequently adjusted using ARCH (Autoregressive Conditional Heteroscedasticity) and GARCH (Generalized Autoregressive Conditional Heteroscedasticity) as an analysis method for data forecasting. Based on the path diagram, it indicatedd that all hypotheses are accepted except for qard al-hasan, which has a significant and negative effect on profitability and stock prices. Therefore, based on these findings, this study contributes to expanding the scope of knowledge in the field of Sharia finance, as well as offers valuable guidance to Islamic finance industries on maximizing Islamic and social instruments to increase profitability, ultimately leading to a positive effect on stock price volatility.